Peningkatan Kompetensi Manajemen Keuangan dan Kewirausahaan pada Usaha Mikro di Desa Rowosari Kabupaten Kendal - Mutamimah Mutamimah; Zaenudin Zaenudin; Sitty Yuwalliatin (Universitas Muhammadiyah Surakarta, 2022)
Limited capital and the low quality of human resources are obstacles to develop micro-enterprises that is managed by fishermen’s wives in Rowosari, Kendal, Central Java. Therefore, it is necessary to economic empowerment in the form of entrepreneurship and business financial management training as well as providing business capital stimulus with the qardhul hasan contract to 20 people. The purpose of this community service, a) Improving entrepreneurial and business financial management knowledge and skills of micro business for fishermen’s wives in Rowosari, b) Motivate and improve entrepreneurial competencies and business financial management competencies for fishermen’s wives in Rowosari, so that they become independent, strong women who can help their family economy and improve their welfare. Qardhul Hasan is a financing for the poor, without collateral and interest, while the borrower is required to return it and pay administrative fees. Qardhul Hasan funds are sourced from zakat, infaq, and sodaqah funds. Community service methods: a). Identifying micro-enterprises that have been carried out by fishermen’s wives in Rowosari, Kendal, Central Java, their potentials and problems, b). Giving a Qardhul Hasan financing collaboration with the Rahmat Semesta Foundation. c). Provide entrepreneurial training and business financial management to them, d). Community services performance evaluation. The results show that after getting a Qardhul Hasan loan and receiving training and assistance in the field of entrepreneurship and business financial management, their entrepreneurial and business financial management knowledge and skill increase and hope that their business develops well and their income and welfare increase.